American labor and economic citizenship : new capitalism from World War I to the Great Depression - Hendrickson, Mark, 1971- (Cambridge University Press, 2013)
Once viewed as a distinct era characterized by intense bigotry, nostalgia for simpler times and a revulsion against active government, the 1920s have been rediscovered by historians in recent decades as a time when Herbert Hoover and his allies worked to significantly reform economic policy. Mark Hendrickson both augments and amends this view by studying the origins and development of New Era policy expertise and knowledge. Policy-oriented social scientists in government, trade union, academic and nonprofit agencies showed how methods for achieving stable economic growth through increased prod.